Business economics [revised syllabus] T.Y.B.Com. - Misra S.K. and Puri V.K. (Himalaya publishing house,Mumbai, 2007)
Commerce
MARATHI
Keywords: Business economics [revised syllabus] T.Y.B.Com.; Commerce; Commerce